2016
DOI: 10.1097/prs.0000000000002782
|View full text |Cite
|
Sign up to set email alerts
|

Breast Tissue Expanders with Magnetic Ports: Clinical Experience at 1.5 T

Abstract: Background: The purpose of this study was to evaluate breast tissue expanders with magnetic ports for safety in patients undergoing abdominal/pelvic magnetic resonance angiography before autologous breast reconstruction. Methods: Magnetic resonance angiography of the abdomen and pelvis at 1.5 T was performed in 71 patients in prone position with tissue expanders with magnetic ports labeled “MR Unsafe” from July of 2012 to May of 2014. Patients were moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“… 5 , 6 , 7 , 8 Of note, in a study of 71 patients with tissue expanders who received abdominal and pelvic magnetic resonance angiography (MRA) at 1.5 Tesla, no patient had magnetic port migration, indicating that adjustments made during magnetic resonance imaging can make this exam safer. 9 …”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 , 7 , 8 Of note, in a study of 71 patients with tissue expanders who received abdominal and pelvic magnetic resonance angiography (MRA) at 1.5 Tesla, no patient had magnetic port migration, indicating that adjustments made during magnetic resonance imaging can make this exam safer. 9 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several higher level-of-evidence studies indicated that patients with TEs with magnetic ports can be scanned safely using MRI: Nava et al [3] found that TEs demonstrated minimal heating and had minor attraction to a 1.5 T static magnetic field and Marano et al [4] similarly found minimal heating and low magnetic field interactions in three TEs tested under 1.5 and 3 T MRI conditions. Furthermore, in a retrospective case series involving 71 patients with 112 TEs, Thimmappa et al [5] reported that abdominal MRA yielded no reports of magnetic port migration or pain. Subsequent surgeon examination of the peri-TE space during autologous breast reconstruction revealed “no evidence of tissue damage, and there were no operative complications at those sites of breast reconstruction.” This group’s experience has further increased to more than 250 patients without substantial complications (personal communication, Martin R. Prince, M.D., Ph.D., Radiology, Weill Cornell Medical Center, NY, 11/01/18).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, despite a careful, systematic review, the controversies regarding the safety of a TE with a magnetic port in the MRI setting remain unanswered. Of note is that, during a period of more than three decades, only two cases reported problems associated with TE exposure to MRI [10,11], while a study conducted in a large series of patients where special precautions were taken to mitigate risks revealed no substantial issues [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients may also have a contraindication to the use of magnetic resonance (MR) in general. This was thought to include patients with breast tissue expanders, which has since been proven not to be the case …”
Section: Imaging Techniques In Microsurgical Breast Reconstructionmentioning
confidence: 99%